Description of two new HLA‐A alleles, HLA‐A*02:572 and HLA‐A*03:225. (13th November 2015) - Balas, A.; García‐Sánchez, F.; Vicario, J. L.
Abstract: Characterization of two new human‐leukocyte antigen (HLA)‐A alleles, A*02:572 and HLA‐A*03:225 .